2015
DOI: 10.1111/jnc.13383
|View full text |Cite
|
Sign up to set email alerts
|

Vinorelbine and epirubicin share common features with polysialic acid and modulate neuronal and glial functions

Abstract: Polysialic acid (PSA), a large, linear glycan composed of 8 to over 100 α2,8-linked sialic acid residues, modulates development of the nervous system by enhancing cell migration, axon pathfinding, synaptic targeting and by regulating differentiation of progenitor cells. PSA also functions in developing and adult immune systems and is a signature of many cancers. In this study we identified vinorelbine, a semi-synthetic third generation vinca alkaloid, and epirubicin, an anthracycline and 4′-epimer of doxorubic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 75 publications
(185 reference statements)
1
11
0
Order By: Relevance
“…5-NOT and vinorelbine were tested in a mouse model of spinal cord injury with immediate application after injury and directly into the lesion site. Compound concentrations used were slightly higher than those with highest impact on neurite growth and neuronal migration in vitro 26 27 and in the range of the PSA mimicking compound tegaserod 21 . Colominic acid was applied in parallel to compare the effects of PSA and the PSA mimicking compounds.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…5-NOT and vinorelbine were tested in a mouse model of spinal cord injury with immediate application after injury and directly into the lesion site. Compound concentrations used were slightly higher than those with highest impact on neurite growth and neuronal migration in vitro 26 27 and in the range of the PSA mimicking compound tegaserod 21 . Colominic acid was applied in parallel to compare the effects of PSA and the PSA mimicking compounds.…”
Section: Resultsmentioning
confidence: 98%
“…Compound concentrations used were slightly higher than those with highest impact on neurite growth and neuronal migration in vitro 2627 and in the range of the PSA mimicking compound tegaserod21. Colominic acid was applied in parallel to compare the effects of PSA and the PSA mimicking compounds.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also considered the cardinal molecule for structural, functional, and synaptic plasticity of the adult nervous system . In order to exploit the vast therapeutic potential of PSA, previous studies have focused on the identification and development of peptide‐based or synthetic PSA mimetics . In a previous study, we observed ∼80% gain of locomotor function in mice after 8 weeks of a single intraoperative application of a synthetic PSA mimetic 5‐nonyloxytryptamine (5‐NOT) following spinal cord compression injury (SCCI) …”
Section: Introductionmentioning
confidence: 99%